The European Union Strategy about the Syrian Regional Crisis. - Διπλαράς, Ευάγγελος (Πανεπιστήμιο Πελοποννήσου, 2019)
This dissertation examines the important issue of the European Union’s (EU) strategy in Syrian regional crisis. In the introduction the dissertation is briefly explained. More specifically, the dissertation comprises of four chapters; in the first chapter, the dissertation examines the concepts of “Conventional Power” and “Civilian Power”. The second chapter, analyzes “The EU and Syrian Crisis from 2011 until 2018”, and presents to a great extent the regional conflict from 2011 until 2018. In the third chapter, three powerful countries, namely France, Germany and the United Kingdom are thoroughly examined. The last part of the dissertation is occupied by the essential bibliography, used in its composition.
Keywords: War--Syria; Syria--Civil War; European Union; Syria; Strategy; Crisis